COVID-associated rhino-orbito-cerebral mucormycosis: A comparative study between computed tomography and magnetic resonance imaging for its early detection in suspected cases of rhino-orbito-cerebral mucormycosis - Priyanka C Megharaj; Vikram M Patil; Santosh Reddy (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: Rhino-orbito-cerebral mucormycosis (ROCM), a life-threatening, acute fungal infection of the nasal cavities and paranasal sinuses, once considered a rare and lethal complication in immunocompromised patients, is now having a massive increase in ROCM incidence in India associated with COVID-19, i.e., COVID-associated mucormycosis with more than 15,000 cases as of May 2021. Early imaging by computed tomography (CT) and magnetic resonance imaging (MRI) is not only helpful in assessing the extent of involvement of this lethal disease but also helps in early diagnosis leading to prompt and aggressive treatment. The present study is aimed at determining and comparing the imaging findings on CT and MRI in ROCM patients, for early diagnosis in suspected cases of ROCM. MATERIALS AND METHODS: The present study is a comparative study of CT and MRI done on 11 patients suspected of ROCM, for 2 months from May to June 2021. RESULTS: Among 11 patients in the study group, ranging from 29 to 65 years of age, 45.4% belonged in 41-60 years of age group, with female predominance. 90.90% cases (10 patients) had maxillary sinus involvement among which 7 cases were diagnosed with ROCM, followed by 63.60% cases (7 patients) had ethmoidal sinus involvement among which 6 cases were diagnosed with ROCM. The involvement of retromaxillary space, pterygopalatine fossa space and masticator space, and cellulitis in premaxillary and preseptal spaces were findings seen only in diagnosed cases of ROCM. Erosions of bones were seen in ROCM cases, 27.20% cases (3 patients) had erosions of walls of maxillary sinus and lamina papyracea each. Orbital involvement in the form of intraconal space and extraocular muscles involvement was seen in 27.20% cases (3 patients) each. Optic nerve involvement was seen in 18.10% cases (2 patients) followed by extraconal space involvement in 9.01% cases (1 patient). Taking KOH staining and/or histopathology (HPR) as standard of reference, CT has a Sensitivity (Sn) of 71.40%, Specificity (Sp) of 100%, Positive predictive value (PPV) of 100%, Negative Predictive Value (NPV) of 66%, and Diagnostic accuracy (DA) of 81% as compared to MRI which has a Sn of 85.7%, Sp of 100%, PPV of 100%, NPV of 80%, and DA of 90.9%. CONCLUSIOIN: CT and MRI play a complementary role in diagnosis of ROCM, as CT is better in detecting bone erosions, whereas MRI is better in detecting soft tissue, orbital and central nervous system involvement. In the acute state of emergency as in the current pandemic with rising cases of ROCM and acute shortage of amphotericin-B, MRI is the single best modality for accurate detection of ROC, helping clinicians in the judicious use of Amphotericin-B.